A Surface Plasmon Resonance Temperature Sensing Unit Based on a Graphene Oxide Composite Photonic Crystal Fiber - Han Liang; Tao Shen; Yue Feng; Zhentao Xia; Hongchen Liu (IEEE Photonics Journal)
A twin-core sensor with high birefringence employing a photonic crystal fiber (PCF) is presented for simulated temperature measurements based on surface plasmon resonance (SPR). The internal wall of the central hole of the PCF is plated with gold and coated with graphene oxide (Au-GO) to develop an SPR sensing channel. The results of a numerical analysis with COMSOL Multiphysics show that the birefringence of this sensing structure can reach 0.0052. In addition, an average sensitivity of −12.695 nm/ °C can be achieved in the range of 0 °C∼80 °C. Compared with uncoated GO sensors and existing sensing units, this sensor shows improved stability, sensitivity and birefringence.